Interaction of citrinin and resveratrol and their effect on Caco-2 cell growth - Ivana BOVDISOVA; Maja GRABACKA; Marcela CAPCAROVA (Journal of Central European Agriculture, 2016)
The aim of this study was to use Caco-2 cells as an in vitro model of human intestinal barrier. This model was employed to investigate interaction of citrinin and resveratrol and to determine the doses that affect cell number. Citrinin (CTN) is a toxic secondary metabolite produced by fungi of the genera Penicillium, Aspergillus and Monascus. It is contaminant of cereals, grains, food and feed products. Previous studies have shown that CTN has teratogenic, nephrotoxic, hepatotoxic and embryotoxic effects. Resveratrol (RES) is polyphenol belongs to the group of stilbenes. At lower doses it has positive effects on human health and higher doses may induce apoptosis. The results of study indicate a significant (P < 0.05) decrease in cell number in all conditions: A (RES 20 μM), B (CTN 100 μg*ml-1), C (CTN 250 μg*ml-1), D (CTN 100 μg*ml-1 + RES 20 μM), E (CTN 250 μg*ml-1 + RES 20 μM) in comparison with the control group of non-treated cells (NT) and control group with ethanol (Ce). A significant (P <0.05) decrease in the cells number was observed between groups A - E, B - C and D - E. Citrinin effect seems to be dose-dependent.